Development of droplet digital PCR assays to quantify genes involved in nitrification and denitrification, comparison with quantitative real-time PCR and validation of assays in vineyard soil - Voegel, Tanja M.; Larrabee, Melissa M.; Nelson, Louise M. (Canadian journal of microbiology, 2021)
Quantifying genes in soil is important to relate the abundance of soil bacteria to biogeochemical cycles. Quantitative real-time PCR is widely used for quantification, but its use with environmental samples is limited by poor reaction efficiencies or by PCR inhibition through co-purified soil substances. Droplet digital PCR (ddPCR) is a technology for absolute, sensitive quantification of genes. This study optimized eight ddPCR assays to quantify total bacteria and archaea as well as the nitrification (bacterial and archaeal amoA) and denitrification (nirS, nirK, nosZI, nosZII) genes involved in the generation or reduction of the greenhouse gas nitrous oxide. Detection and quantification thresholds were compared with those of quantitative real-time PCR and were equal to, or improved, in ddPCR. To validate the assays using environmental samples, soil DNA was isolated from two vineyards in the Okanagan valley in British Columbia, Canada, over the 2017 growing season. Soil properties related to the observed gene abundances were determined. Total bacteria, nirK, and nosZII increased with time and the soil C/N ratio and NH 4 + -N concentration affected total archaea and archaeal amoA negatively. The results, compared with those of other studies, showed that ddPCR is a valid alternative to qPCR to quantify genes involved in nitrification or denitrification.